Forming of Historical and Cultural Landscape of Yakuts: Ethno-Local Models and Spatial Concepts - N. K. Danilova (Научный диалог)
The strategies of space development, mechanisms of adaptation and identification of local cultures of the Sakha (Yakut) people in constant close connection with the natural environment are considered. The invariant features of the ethno-cultural landscape of the Yakuts, formed on the basis of local worldview, are revealed. The material for cross-cultural research was folklore, ethnographic and linguistic data reflecting and revealing the fundamental and symbolic meanings of the dominant symbols of spaces and ecological traditions based on the spiritualization of the landscape environment. The novelty of the study is seen in the fact that the work for the first time analyzes natural objects (alas, forest, ponds, mountain), which played a key role in the formation of local identities, in the semantic context. Historical-cognitive and linguistic analysis of the mental-cultural layer of natural objects showed that the cultural model of the Yakuts preserved archaic elements associated with the Turkic-Mongolian substrate. It is shown that the Yakuts transferred the metaphor of the South and stereotypes of spatial behaviour based on the perception of the southern ancestral home to a new geographical space. The author argues that natural objects accumulate ideas about the habitable terrain and “feeding landscape” and become key ethno-differentiating markers and the basis of the national-cultural narrative of the Yakut people. Thus, the conceptual foundations for the perception of natural objects in the minds of the Yakut people are determined, on the one hand, by utilitarian ideas about the territory as an economically developed space, on the other hand - by the mythological perception of real geographical space as value-heterogeneous loci according to the universal division of “own / alien.”